Cognitive analysis of the development of human resource competencies in line with the Fourth Industrial Revolution - Habib Zare ahmadabadi; Sayed Heidar Mirfakhraddini; Fatemeh Zamzam; somayeh amirhosseini (مدیریت بهره وری)
Currently, the world is living in the era of the fourth industrial revolution. Although this era provides many opportunities for companies and organizations due to technological advances, it also presents many challenges. One of these challenges is the need for a set of new competencies that occur due to the transformation of the nature of jobs through digitalization in Industry 4.0. Hence, the purpose of the current research is to identify the skills needed in Industry 4.0 and provide a cognitive analysis of it. This research is classified as applied research and employs an exploratory mix method approach regarding data collection. The statistical population for this research includes experts in the steel industry (middle to upper managers). A sample of 10 experts from this sector were selected to complete the questionnaire, using a purposeful sampling method. Then, using the opinions of 10 experts of the steel industry in Yazd province, the collected data have been analyzed through the methods of intuitive fuzzy TOPSIS and intuitive fuzzy cognitive map. The competencies of Industry 4.0 in the steel industry were prioritized through intuitive fuzzy TOPSIS and the relationships between measures to improve competencies were explained using the intuitive fuzzy cognitive mapping method. The obtained findings indicate that the index of willingness of managers and owners of companies to move towards intelligentization and the creation of smart factories is more central than other measures, and as a result, more attention should be paid to it. Also, in the prioritization of competencies, it was found that customer-oriented competency has the highest priority. Key Words: Industry 4.0, intuitive fuzzy TOPSIS, human resources competencies, Fourth Industrial Revolution, intuitive fuzzy cognitive map   1.Introduction The world we are in now has gone through stages of progress and has reached a new stage of evolution, innovation and transformation. Today, this intelligent development is known as the Fourth Industrial Revolution. Organizations should identify the benefits of Industry 4.0 and train their human resources to deal with technological advances. This development not only requires the development of technical skills but also emphasizes the importance of developing human resources to maintain the organizational performance. Improving human resources at behavioral, organizational and technological levels will be required during implementation process. Due to the fourth industrial revolution and automation and advanced systems, the previous skills and competences of the employees will no longer be effective and appropriate. Therefore, the managers of the organizations should look for employees who have new competencies that are suitable for Industry 4.0 to guarantee the success of their organization. In this regard, the purpose of the current research is to identify and rank the required human resource competencies in line with the fourth industrial revolution and determine how to achieve these competencies in the steel industry of Yazd province in the form of measures/policies. In addition, it is necessary to prioritize these competencies for use in the field of recruiting and hiring employees of organizations, which, in turn, helps policymakers to plan the movement in the direction of the fourth industrial revolution. Literature Review The vital and pervasive role of human resources in organizations is evident to all. Caregiver competencies are extremely important in any organization and determine the success of that organization. This is especially evident during the fourth industrial revolution. Although researchers have focused on the technical and economic aspects of this revolution in the past studies, less attention is paid in research to the role of human resources (Gupta et al., 2021). The following provides a summary of studies conducted in the field of human resources. In their research, Hecklau et al. (2016) first collected a comprehensive list of competencies required to work in the digital world, and then, depicted all the competencies identified in the image, and finally discussed the merits of the model as an applied strategy. Kazankoglu and Özkan Ozen (2018) presented a competency model for Industry 4.0 workforce in their research. In another research, Jerman et al. (2018) contributed to the body of knowledge about Industry 4.0 phenomena by collecting the skills needed in smart factories in the future. Vrchota et al. (2019), in their research emphasized the assumptions of human capital and its readiness for Industry 4.0 in the Czech Republic. Also, Sapper et al. (2021), in their research, stated that competencies, such as willingness to learn, understanding the comprehensive process, interdisciplinarity, and communication skills are of great importance. Kipper et al. (2021) showed in a research that the main competencies needed include leadership skills, self-organization, creativity, problem solving, teamwork, etc. Finally, in the review of the literature and the background of the research in the field of competencies needed by human resources in the fourth industrial revolution, 60 competencies of human resources in the fourth industrial revolution and 19 measures to improve these competencies were identified. Methodology Given that the current research aims to identify the required competencies of human resources in the context of the fourth industrial revolution and to examine the current situation and the significance of these competencies in the steel industry of Yazd province, it is exploratory in nature, with a practical purpose and employs a mixed-methods approach for data collection. Also, in terms of the time horizon, it is one-time because it was done only at a specific time and will not be repeated during other time periods. The statistical population of the research includes all academic experts and managers in the field of industrial logistics 4.0 in the steel industry, who participated in completing the questionnaire using the purposeful sampling method. The research methodology is as follows: first, in order to access the researches and articles conducted in the investigated field, two databases, scopus and google scholar, have been searched in two bases of the combination of keywords (competenc* OR "necessary skills" OR abilities AND "Industry 4.0" AND "Human Resources").  The title, abstract and keywords of the articles were used as the criteria for entering the articles into the research. The exclusion criteria of the articles were also performed in three stages by screening the title, abstract and the entire text of the article. In general, researchers look at the issue of introducing variables and indicators that represent the competencies of human resources in Industry 4.0 (not their research methods). In total, 117 articles were found in the scopus database and 70 articles in the google scholar database. After searching and removing duplicate entries across two databases, 76 items were identified as appropriate and relevant. In the following stage, after analyzing the content of the studies by examining their titles, abstracts and full texts, the cases with irrelevant and incomplete content and duplicates were removed. Finally, 12 articles with most relevant and specialized content on Industry 4.0 competencies were used in order to extract competencies. Then, based on the identified indicators, a questionnaire was compiled and administered to collect the opinions of steel industry experts. Furthermore, with the help of intuitive fuzzy TOPSIS method, human resources competencies were prioritized in line with Industry 4.0 in the steel industry. Also, through the intuitive fuzzy cognitive map, the roadmap for the improvement of industry 4.0 competencies in the steel industry was developed. Result In the first step of the current research, by reviewing the related literature and research background, a total of 60 competencies of human resources were identified in line with the fourth industrial revolution, as well as 19 measures to improve these competencies. Following this, 19 identified measures were compiled in the form of a questionnaire and given to 10 experts of steel industry in Yazd province. Then, in Excel software, the steps of the fuzzy cognitive mapping method were implemented on the data obtained from this questionnaire. After establishing the final success matrix (FMS), the data from this matrix was input into the FCMappear software and subsequently, using the software pajek, the mapping between concepts was created. Next, in order to improve the skills in this industry, a road map was prepared by developing a scenario. In the next step, 60 extracted competencies were compiled in the form of a questionnaire and given to 10 steel industry experts in Yazd province. They were asked to rate the importance of each of these competencies in a five-point range from very high (9), to high (7) and to very low (1).  Finally, according to the opinion of the experts, the competencies were prioritized using the intuitive fuzzy TOPSIS method, among the 60 competencies, customer oriention with a relative coefficient of 0.772 , process understanding/management index with a relative coefficient of 0.661, IT skills index with a relative coefficient of 0.66, leadership skills with a coefficient of 0.633 and understanding of information technology security with a relative coefficient of 0.629, were identified as the top five competencies of human resources in line with the industrial revolution 4.0. Other competencies were identified and assigned to subsequent priority levels based on the investigation. Discussion Considering the examination of the important measures to improve the competencies of human resources in line with the fourth industrial revolution in the mentioned scenarios and the top competencies of the TOPSIS method, it can be found that the competencies of understanding the security of information technology and IT skills, which are among the most important competencies, are effective in solving  security issues such as data hacking or cyber security for the adoption and deployment of Industry 4.0. Also, having appropriate skills of current knowledge, programming knowledge and the ability to process and analyze data leads to the inclination of companies, in particular, the personnel related to technology management to develop technology instead of buying technology. On the other hand, it also leads to the growth and stabilization of the company's R&D unit in the fields of computer science and sciences related to Industry 4.0. Additionally, the influence of the competences of motivation and willingness to learn, adaptability, ability to compromise and cooperate, belief and trust in new technologies can be emphasized to conduct educational programs and seminars in the field of digitization and automation. Furthermore, the acceptance of employees in relation to the changes related to the digitization process and the application of technologies related to Industry 4.0 at the company level should not be overlooked. In conclusion, the obtained results suggest that to attract and hire human resources with the competencies of Industry 4.0, the steel industry needs to consider candidates’ technical or professional competencies along with their methodological, social and personal characteristics during the recruitment process. Also, with the aim of improving the skills of Industry 4.0 of the workforce working in the steel industry, it is recommended that the managers and specialists of this industry provide training opportunities and workshops to acquire these skills.